2003
DOI: 10.1046/j.1365-2044.2003.02788_3.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neuromuscular blockade on the efficiency of mask ventilation of the lungs*

Abstract: SummaryMathematical formulae to calculate body surface area from measurements of height, weight and other parameters date from the late 19th century. Drug doses, fluid therapy, caloric requirements and physiological parameters such as cardiac output, glomerular filtration rate and a variety of respiratory function parameters are all frequently expressed in terms of a body surface area. Body surface area is often used in preference to body mass (weight). However, the original rationale for using body surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 12 publications
0
46
2
1
Order By: Relevance
“…Rapid sequence induction accounted for most occasions when thiopental was administered, and this combination appeared to be an important risk factor for AAGA. Relevant questions include: whether co-administration of opioids or other adjuncts lowers the risk of AAGA while still achieving the goals of rapid sequence induction; whether there is time to assess the effect of the induction agent and provide more if needed; whether the administration of the rapidly acting neuromuscular blocking drug can be delayed slightly to check the conscious level, and/or even check the ease of bag-mask ventilation [35][36][37][38], itself a test of depth of anaesthesia; and whether thiopental should continue to have a place. The high proportion of AAGA cases associated with failed, prolonged or difficult airway management indicates an overlap between the findings of NAP4 [39] and NAP5.…”
Section: Induction Of Anaesthesia and Transfer To Theatrementioning
confidence: 99%
“…Rapid sequence induction accounted for most occasions when thiopental was administered, and this combination appeared to be an important risk factor for AAGA. Relevant questions include: whether co-administration of opioids or other adjuncts lowers the risk of AAGA while still achieving the goals of rapid sequence induction; whether there is time to assess the effect of the induction agent and provide more if needed; whether the administration of the rapidly acting neuromuscular blocking drug can be delayed slightly to check the conscious level, and/or even check the ease of bag-mask ventilation [35][36][37][38], itself a test of depth of anaesthesia; and whether thiopental should continue to have a place. The high proportion of AAGA cases associated with failed, prolonged or difficult airway management indicates an overlap between the findings of NAP4 [39] and NAP5.…”
Section: Induction Of Anaesthesia and Transfer To Theatrementioning
confidence: 99%
“…We appreciate the interest Dr Xue et al have taken in our recent article [1]. Our study was designed to assess the effect of neuromuscular blockade on facemask ventilation and we found that the former facilitates the latter.…”
Section: A Replymentioning
confidence: 81%
“…In our own earlier study [1], checkers offered a different and more accurate argument: that if a difficult airway was predicted, mask ventilation will maintain oxygenation from the earliest opportunity while anaesthesia is deepened [3]. This logic of 'checkers' also makes proper distinction between short-and long-acting NBDs.…”
Section: A Replymentioning
confidence: 99%
See 1 more Smart Citation
“…4 informs the debate concerning the role of checking the ability to mask-ventilate the lungs before administering neuromuscular blockade. Although some experimental results suggesting an improved ability to mask ventilate after neuromuscular blockade have been interpreted to imply that this 'checking' is not necessary [14,15], this is probably over-ridden by the theoretical considerations. If we do not know whether we can maintain oxygenation by mask ventilation, but proceed nonetheless to administer a long-acting neuromuscular blocking drug, and if we subsequently find inability to intubate the trachea and mask ventilate, then we have created a situation in which obstructive apnoea and the physiology described in this article ensues.…”
Section: Relevance To the 'Can't Intubate Can't Ventilate' Situationmentioning
confidence: 99%